Penentuan Opsi Investasi Optimal pada Pasar Modal Volatil: Analisis Maximax, Maximin, dan Minimax Regret - Akbar, Rahmat; Mar'aini; Jusmarni (Jurnal Pustaka Manajemen (Pusat Akses Kajian Manajemen), 2025)
The increasing volatility of the capital market driven by global economic uncertainty requires investors to select optimal investment options despite limited information. This study aims to analyze investment decision-making using three primary approaches under uncertainty: the Maximax, Maximin, and Minimax Regret methods. The data consist of historical returns from several large-cap stocks listed on the Indonesia Stock Exchange (IDX) over the past three years, which show substantial fluctuations. The analysis compares payoff values under different market conditions (optimistic, moderate, and pessimistic) and calculates regret levels to identify the most efficient investment alternative. The findings indicate that the Maximax method favors high-risk stocks with the highest potential returns, the Maximin method prioritizes stable defensive stocks, while Minimax Regret offers the most balanced decision by accounting for potential opportunity losses. Managerial implications highlight the importance of understanding investor risk profiles when formulating investment strategies and the need for financial institutions to provide uncertainty-based analytical tools. This study contributes to the investment decision-making literature in volatile markets by demonstrating the applicability of classical uncertainty decision models in generating adaptive and measurable investment strategies.